Imagination and Experience (Taylor & Francis, 2024)
This volume brings together two philosophical research areas that have been subject to increased attention: work regarding the unique character of having an experience and studies on the nature and powers of imagination. The importance of imagination seems to stand in tension with the assumed unique and irreplaceable role of experience in our lives. However, new arguments in various philosophical debates suggest that there is a need to examine how both areas of research interrelate and can enrich one another. The chapters in this volume examine whether the traditional accounts of experience and imagination need to be challenged. They are divided into thematic sections that discuss epistemological, ontological, normative, phenomenological, and intersubjective questions related to experience and imagination. Imagination and Experience is an essential resource for scholars and advanced students working in philosophy of mind, epistemology, ethics, aesthetics, and philosophy of psychology.